Psychometric properties of multicomponent tools designed to assess frailty in older adults: A systematic review. Issue 1 (December 2016) - Sutton, Jennifer; Gould, Rebecca; Daley, Stephanie; Coulson, Mark; Ward, Emma; Butler, Aine; Nunn, Stephen; Howard, Robert
Abstract Background Frailty is widely recognised as a distinct multifactorial clinical syndrome that implies vulnerability. The links between frailty and adverse outcomes such as death and institutionalisation have been widely evidenced. There is currently no gold standard frailty assessment tool; optimizing the assessment of frailty in older people therefore remains a research priority. The objective of this systematic review is to identify existing multi-component frailty assessment tools that were specifically developed to assess frailty in adults aged ≥60 years old and to systematically and critically evaluate the reliability and validity of these tools. Methods A systematic literature review was conducted using the standardised COnsensus‐based Standards for the selection of health Measurement INstruments (COSMIN) checklist to assess the methodological quality of included studies. Results Five thousand sixty-three studies were identified in total: 73 of which were included for review. 38 multi-component frailty assessment tools were identified: Reliability and validity data were available for 21 % (8/38) of tools. Only 5 % (2/38) of the frailty assessment tools had evidence of reliability and validity that was within statistically significant parameters and of fair-excellent methodological quality (the Frailty Index-Comprehensive Geriatric Assessment [FI-CGA] and the Tilburg Frailty Indicator [TFI]). Conclusions The TFI has the most robust evidence of reliability and validity and has been the most extensively examined in terms of psychometric properties. However, there is insufficient evidence at present to determine the best tool for use in research and clinical practice. Further in-depth evaluation of the psychometric properties of these tools is required before they can fulfil the criteria for a gold standard assessment tool.